Silica Gel-Supported Polyphosphoric Acid: A Mild, Efficient and Reusable Catalyst for the One-Pot Synthesis of 1,2,4,5-Tetrasubstituted Imidazoles - Tavakoli-Hoseini, N.; Davoodnia, A. (Asian Journal of Chemistry, 2010)
An efficient and convenient method for the synthesis of 1,2,4,5-tetrasubstituted imidazoles has been developed by a one-pot multi-component reaction of benzil, aromatic aldehydes, primary amines and ammonium acetate in the presence of silica gel-supported polyphosphoric acid (PPASiO2), as a green and reusable catalyst under solvent-free conditions. The present methodology offers several advantages such as simple procedure with an easy work-up, relatively short reaction times and high yields.